Digital Promotion, Ease of Use, and Trust in Shaping Perceived Consumer Purchase Intention: Evidence from MSME Owners in Fatukoa Village, Kupang City - Maria Imakulata Pongge; Heni Haryati Lassa; Adrianus Ketmoen (Poltanesa, 2026)
This study analyzes the effect of digital media-based promotion, perceived ease of use, and trust on perceived consumer purchase intention from MSME owners’ perspective in Fatukoa Village, Kupang City. The study is based on the increasing need for local MSMEs to adopt digital promotion strategies as market interaction becomes more connected to online platforms. A quantitative approach with an associative-verificative design was applied. Data were collected from 68 MSME owners selected through purposive sampling, with criteria including business actors who had used digital media for promotion or sales activities. The data were gathered through structured questionnaires and analyzed using multiple linear regression. The findings show that digital media-based promotion has a positive and significant effect on perceived consumer purchase intention, indicating that attractive, informative, and consistent promotional content strengthens MSME owners’ assessment of consumer purchase interest. Trust also has a positive and significant effect, showing that seller honesty, transaction security, product quality consistency, and business reputation are important in shaping perceived consumer purchase intention. Meanwhile, perceived ease of use has a significant but negative effect, indicating that ease of using digital platforms alone does not automatically strengthen perceived consumer purchase intention. Simultaneously, the three variables significantly influence perceived consumer purchase intention, although the R Square value of 24.6% shows that other determinants remain outside the model. These findings contribute to MSME digital marketing literature by offering an actor-based perspective, where purchase intention is understood as MSME owners’ assessment of observable consumer responses rather than direct self-reported intention from consumers.